The Role of the ChatGPT AI Application in Enhancing the Performance of Computer Trainers at the Technical College in Mecca - Al-Meqati, Sami Munahi (Journal of engineering sciences and information technology, 2025)
This study aimed to examine the impact of using the ChatGPT application in developing the training performance of computer trainers at the Technical College in Makkah. To achieve this objective, the researcher employed the descriptive analytical approach and designed a questionnaire consisting of (18) items distributed across five main axes: use of ChatGPT in training, educational interaction, training efficiency, technical challenges, and perceived positive effects. The instrument was applied to a sample of (40) trainers. Data were analyzed using frequencies, percentages, means, standard deviations, Pearson correlation coefficient, and simple linear regression analysis. The results revealed that the use of ChatGPT has a clear positive effect on enhancing training performance, particularly in improving content quality and increasing interaction. The findings also indicated a high level of awareness among trainers regarding the positive effects of the application, while technical challenges were not statistically significant. The study recommended integrating artificial intelligence tools into technical training environments and providing training programs to support their effective use.
Keywords: Artificial Intelligence; ChatGPT; Training Performance Improvement; Technical College